A dual heavy ion beam probe diagnostic on the TJ-II stellarator - Chmyga, O.O.; Ascasibar, E.; Barcala, J.; Drabinskiy, M.A.; Eliseev, L.G.; Hidalgo, C.; Khabanov, P.O.; Khrebtov, S.M.; Komarov, O.D.; Kozachok, O.S.; Krupnik, L.I.; Lysenko, S.E.; et al. (Вопросы атомной науки и техники, 2019)
The aim of the report is to show the development of HIBP diagnostics on the TJ-II stellarator and, as a result, the expansion of the range of plasma parameters measurements. The first Heavy Ion Beam Probe (HIBP-1) diagnostic is being used on TJ-II stellarator since 2000. It has been shown significant progress in the measurements of plasma profiles and oscillations. The second HIBP-2 system was installed on TJ-II in 2012. Dual HIBP system, consisting of two identical HIBP-1 and HIBP-2 located ¼ torus apart, provides the measurement of the long-range correlations of plasma parameters in the full plasma column. Low noise high gain (10⁷ V/A) preamplifiers with 1 Hz bandwidth sampling is used. They allow to study broadband turbulence and quasi-coherent modes like geodesic acoustic modes, Alfven eigenmodes, suprathermal electron induced modes, etc. New capabilities of the dual HIBP diagnostic in plasma potential and density investigations were demonstrated on TJ-II stellarator in the measurements of the correlation between fluctuations in different poloidal and toroidal locations: on the same field line, on the same magnetic surface or on different magnetic surfaces at different points, separated toroidally and/or poloidally. На стелараторі TJ-II створена подвійна система зондування плазми пучком важких іонів (ЗППВІ). Система складається з двох ідентичних комплексів, розташованих на відстані ¼ тора. Перший діагностичний комплекс почав діяти в 2000 році. Другий комплекс був встановлений в 2012 році. Використання підсилювачів детекторних сигналів з низьким рівнем шуму (10⁷ В/A) з пропускною здатністю 1 МГц дозволяє вивчати широкосмугову турбулентність та квазікогерентні режими, такі як геодезичні акустичні моди; альфвенівські моди; супертермальні моди, які збурюються швидкими електронами, тощо. Нові можливості подвійної системи були продемонстровані при вимірюваннях далеких кореляцій між флуктуаціями в різних полоїдальних та тороїдальних місцях: на одній лінії магнітного поля, на одній або на різних магнітних поверхнях у різних точках, розташованих тороїдально та/або полоїдально. На стеллараторе TJ-II создана двойная система зондирования плазмы пучком тяжелых ионов (ЗППТИ). Система состоит из двух идентичных комплексов, расположенных на расстоянии ¼ тора. Первый диагностический комплекс начал действовать в 2000 году. Второй комплекс был установлен в 2012 году. Использование усилителей детекторных сигналов с низким уровнем шума (10⁷ В/A) и полосой пропускания 1 МГц позволяет изучать широкополосную урбулентность и квазикогерентные моды, такие как геодезические акустические моды; альфвеновские собственные моды; моды, индуцированные надтепловыми электронами и т.д. Новые возможности двойной системы были продемонстрированы при измерениях дальних корреляций между флуктуациями, измеренными в различных полоидальних и тороидальных положениях: на одной или на разных магнитных поверхностях, в различных точках, смещенных тороидально и/или полоидально.